Antitumor effect of insulin‐like growth factor‐1 receptor inhibition in head and neck squamous cell carcinoma. (21st August 2019) - Lehman, Christine E.; Khalil, Ashraf A.; Axelrod, Mark J.; Dougherty, Michael I.; Schoeff, Stephen S.; Taniguchi, Linnea E.; Mendez, Rolando E.; David, Abel P.; McGarey, Patrick O.; Hubbard, Matthew A.; Donaldson, Lane; Frierson, Henry F.; et al.
Abstract : Objectives: The insulin‐like growth factor‐1 receptor (IGF1R) has been implicated in therapeutic resistance in head and neck squamous cell carcinoma (HNSCC), and small molecule tyrosine kinase inhibitors (TKIs) of IGF1R activity may have anticancer activity. Therefore, the relationship between survival and IGF1R expression was assessed for oral cavity (OC) cancer, and the antitumor effects of two IGF1R‐TKIs, OSI‐906 and BMS‐754807, were evaluated in HNSCC cell lines in vitro. Methods: Clinical outcome data and tissue microarray immunohistochemistry were used to generate IGF1R expression‐specific survival curves. Immunoblot, alamarBlue proliferation assay, trypan blue exclusion viability test, clonogenic assay, flow cytometry, and reverse phase protein array (RPPA) were used to evaluate in vitro responses to IGF1R‐TKIs. Results: For patients with stage III/IV OCSCC, higher IGF1R expression was associated with poorer overall 5‐year survival ( P = 0.029). Both BMS‐754807 and OSI‐906 caused dose‐dependent inhibition of IGF1R and Akt phosphorylation and inhibited proliferation; BMS‐754807 was more potent than OSI‐906. Both drugs reduced HNSCC cell viability; only OSI‐906 was able to eliminate all viable cells at 10 μM. The two drugs similarly inhibited clonogenic cell survival. At 1 μM, only BMS‐754807 caused a fourfold increase in the basal apoptotic rate. RPPA demonstrated broad effects of both drugs on canonical IGF1R signaling pathways and also inhibition of human epidermal growth factor receptor‐3 (HER3), Src, paxillin, and ezrin phosphorylation. Conclusion: OSI‐906 and BMS‐754807 inhibit IGF1R activity in HNSCC cell lines with reduction in prosurvival and proliferative signaling and with concomitant antiproliferative and proapoptotic effects. Such antagonists may have utility as adjuvants to existing therapies for HNSCC. Level of Evidence: NA Laryngoscope, 130:1470–1478, 2020